2016
DOI: 10.15252/embr.201541643
|View full text |Cite
|
Sign up to set email alerts
|

SIRT5 promotes IDH2 desuccinylation and G6PD deglutarylation to enhance cellular antioxidant defense

Abstract: Excess in mitochondrial reactive oxygen species (ROS) is considered as a major cause of cellular oxidative stress. NADPH, the main intracellular reductant, has a key role in keeping glutathione in its reduced form GSH, which scavenges ROS and thus protects the cell from oxidative damage. Here, we report that SIRT5 desuccinylates and deglutarylates isocitrate dehydrogenase 2 (IDH2) and glucose-6-phosphate dehydrogenase (G6PD), respectively, and thus activates both NADPH-producing enzymes. Moreover, we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
163
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(171 citation statements)
references
References 43 publications
7
163
0
1
Order By: Relevance
“…It has been proven that G6PD acetylation on K 403 affects the formation of active dimers, which decreases G6PD activity (15). Conversely, 2 other studies have reported that glycosylation on Ser and sirtuin 5‐associated deglutarylation of G6PD increase G6PD activity (48, 49). In this study, we present a novel finding for the regulation of the G6PD protein.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been proven that G6PD acetylation on K 403 affects the formation of active dimers, which decreases G6PD activity (15). Conversely, 2 other studies have reported that glycosylation on Ser and sirtuin 5‐associated deglutarylation of G6PD increase G6PD activity (48, 49). In this study, we present a novel finding for the regulation of the G6PD protein.…”
Section: Discussionmentioning
confidence: 94%
“…G6PD is subject to complex regulation, and modifications of G6PD protein have been reported (15, 48, 49). It has been proven that G6PD acetylation on K 403 affects the formation of active dimers, which decreases G6PD activity (15).…”
Section: Discussionmentioning
confidence: 99%
“…However, these sirtuins may contribute to ROS homeostasis based on their targets. For example, SIRT5 may act in parallel to SIRT3 via deacetylation of FOXO3A and desuccinylation of IDH2 [46,47]. Likewise, SIRT4 may affect ROS via pyruvate dehydrogenase complex (PDH), glutamate dehydrogenase (GDH) and fatty acid oxidation through malonyl-CoA decarboxylase (MCD) [4850].…”
Section: Mitochondrial Sirtuins Protect Against Age-related Diseasesmentioning
confidence: 99%
“…It also functions in glycolysis and TCA cycle by controlling the PTM level of succinate dehydrogenase complex (GDH), pyruvate dehydrogenase complex (PDH), and GAPDH (29,30). In response to oxidative stress, SIRT5 desuccinylates superoxide dismutase [Cu-Zn] (SOD1), isocitrate dehydrogenase 2 (IDH2), and deglutarylates glucose-6-phosphate 1-dehydrogenase (G6PD) to maintain cellular redox homeostasis (31,32). SIRT5 may play a role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%